(HI)STORIES - Berriet, Margalit (Design/Arts/Culture, 2023)
The purpose of this paper is to journey through the world of abstract signs, symbols, and images, in an attempt to comprehend the process of constitution of memories, of (hi)stories, of dialects, and of (super)natural realities, as generated by human perceptions of things. Sensitivity and intuition in the process of recording impressions of spaces and places, of nature and of objects, are integral parts of the process of generating and storing memories, shaping associations, and fashioning the storylines that compose our (hi)stories. These are also the sources for comprehending the process by which the mind produces images and other means of communication inventing signs and symbols, composing messages, languages, technologies, and arts. The need to leave a trace is instinctive. Human beings are defined by their capacities to observe, propose ideas, defend hypotheses, and prove objectives. Artistic images and creations, from pre-history to today, convey thoughts, facts, and memories, making the incredible diversity of the human spirit visible. All human actions are based upon cultural, social, and ethical constructions of knowledge, interpretations, awareness, and of engagements. Arts and cultures, then, are mirrors of the journey of civilization, reflecting on the entirety of its expeditions and productions. Imagery and metaphor connect people, continents, philosophies, beliefs, (hi)stories. Languages and arts transcend locations and personal differences, illustrating and enhancing the understanding of realities, ethics, and aesthetics. Nowhere on earth do people exist without language, art, or culture.